Pemanfaatan E-book Kolaborasi Sekolah dan Orangtua dalam Pemantauan Konsistensi Perilaku Siswa Autis - Imaniar Purbasari; Nur Fajrie (Lembaga Pengembangan Kinerja Dosen, 2026)
Inclusive education in Indonesia places autistic children as one of the main focuses, especially related to communication difficulties, social interaction, and behavior. The number of autistic children continues to increase every year with the predominance of boys. The Applied Behavior Analysis (ABA) method developed by Loovas is adapted to help monitor the development and behavior of autistic children consistently at home and school. Monitoring activities are carried out through three stages: (1) assistance in the use of collaborative e-books to monitor the consistency of the behavior of autistic students, (2) the implementation of collaborative e-books through ABA therapy to parents to improve the consistency of children's behavior, and (3) evaluation and dissemination of the use of collaborative e-books for parents. The results of the activity showed that collaborative e-book products through ABA therapy were successfully implemented as practical guidelines for schools and parents. In addition, a supporting device in the form of a monitoring system website functions as a digital platform to document, monitor, and evaluate the development of children's behavior synchronously between home and school. Training on the use of e-books and monitoring systems improves the consistency of autistic children's behavior so that self-development independence is formed. The use of e-books has been proven to increase self-independence, behavioral adjustment, social interaction, and consistent repetitive activities in supporting the development of autistic children.